Compounding and the structure of the Tani lexicon - Post, Mark (2024)
Compounding in Tani appears to have been a process of disyllabification, where monosyllabic forms in Proto-Tani have been lexicalised as compounds. This has resulted in a interesting division in the Tani languages, with nouns and adjectives on the one hand being closely aligned, and verbs on the other behaving quite differently. This division is interesting because of the more usual alignment in Asian languages of adjectives with verbs, not nouns. The story of this division is traced through the lexicon, with evidence from morphology, tone, segmental phonology and syllable structure, all showing a shift towards greater agglutination in Tani languages.